Asset Growth and Stock Market Returns: A Time-Series Analysis. (11th June 2018) - Wen, Quan
Abstract: I find that aggregate asset growth constructed from bottom-up data negatively predicts future market returns both in and out-of-sample and this result is robust across G7 countries. I further show that aggregate asset growth contains information about future market returns not captured by traditional macroeconomic variables and other measures of investment or growth. The forecasting ability of asset growth is strongly correlated with its propensity to predict more optimistic analyst forecasts and subsequent downward revisions, earnings surprise, and systematic errors in investors' expectations. The time-varying risk premium also appears key in explaining the documented return predictability.